Faktor Keluarga, Media, dan Teman dalam Pemilihan Makanan pada Mahasiswa PPKU IPB - Laras Aulia; Lilik Noor Yulianti (Jurnal Ilmu Keluarga dan Konsumen, 2018)
This study aimed to analyze the influence of family factors media and friends on college student's food choice specifically vegetables. Family factors are assessed from parenting style and parent communication patterns while media and friend factors are judged from the exposure of information obtained by the students. Design of this study was using a quantitative survey. Data were collected by self-administered involving 288 first-year students selected by cluster random sampling. Data were analyzed using descriptive analysis, a different test, and multiple linear regression test. The results showed there was a change in eating habits of students before and after IPB. Before entering the IPB male students tend to eat vegetables with half a bowl serving, while the female students eat vegetables with a serving of one bowl. Almost all student parenting styles applied by parents of male and female students are authoritative parenting style. The results of this study show that more than three-quarters of male and female students have a type of communication pattern of conversation orientation. Male and female students tend to be exposed to information through the media rather than by friends. There is no difference in the exposure of information through media and friends between men and women. This study found three main reasons for the selection of food, especially vegetables in the students of health, mood, and weight control. The results of multiple linear regression test showed that the selection of eating vegetables in students influenced by authoritative parenting style, media, and gender.